Quadrupole moment of 14B exotic nucleus - Manie, N. S. (Iraqi Journal of Physics, 2019)
The quadrupole moment of 14B exotic nucleus has been calculated using configuration mixing shell model with limiting number of orbital's in the model space. The core- polarization effects, are included through a microscopic theory which considers a particle-hole excitations from the core and the model space orbits into the higher orbits with 6ħω excitations using M3Y interaction. The simple harmonic oscillator potential is used to generate the single particle wave functions. Large basis no-core shell model with (0+2)ћω truncation is used for 14B nucleus. The effective charges for the protons and neutrons were calculated successfully and the theoretical quadrupole moment was compared with the experimental data, which was found to be in a good agreement.